1986
DOI: 10.1080/03079458608436268
|View full text |Cite
|
Sign up to set email alerts
|

Incidence ofCampylobacterspp. in broiler flocks monitored from hatching to slaughter

Abstract: SUMMARYThe incidence of Campylobacter jejuni/coli was examined in five flocks of broilers monitored from hatch to slaughter, in feed and water and in litter samples. A total of 1440 samples from 720 broilers was examined. Campylobacter spp. were not isolated from broiler chicks at 1 day of age and were only isolated from one broiler chick in one flock at 1 week of age. In three flocks Campylobacter spp. were isolated from all chicks sampled at 4 weeks of age. In the fourth flock all chicks sampled were negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 14 publications
4
27
0
1
Order By: Relevance
“…Once campylobacter was isolated from a flock, all broilers in that particular broiler house became colonized within 1 week, and isolation rates in the flocks remained at 100 % up to the time of slaughter. Similar findings, both on the time of first detection and isolation rates within flocks, have been reported in other longitudinal studies [1,15,16]. However, not all broiler flocks were found to be campylobacter-positive at the end of the production cycle.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Once campylobacter was isolated from a flock, all broilers in that particular broiler house became colonized within 1 week, and isolation rates in the flocks remained at 100 % up to the time of slaughter. Similar findings, both on the time of first detection and isolation rates within flocks, have been reported in other longitudinal studies [1,15,16]. However, not all broiler flocks were found to be campylobacter-positive at the end of the production cycle.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of campylobacter-positive broiler flocks were colonized with more than one serotype at the same time, as has been observed in other studies [15,18]. The serotype distribution within a flock sometimes changed during the production cycle.…”
Section: Discussionsupporting
confidence: 75%
“…During the slaughter, poultry carcasses become contaminated by the release of intestinal contents or transfer of contamination from the surface flora of the birds [11]. Some investigators [3,6,12,20] found that C. jejuni had already spread at the farm level; but the epidemiology of C. jejuni in broilers and its ecology in farm practices have not been completely defined. The source of C. jejuni contamination at the broiler-growing level is not clear.…”
Section: Methodsmentioning
confidence: 99%
“…C. jejuni contamination of poultry meat during processing has been well documented [3,18,24,34]. It is also well known that broilers on growing farms are often infected with C. jejuni or C. coli [5,6,11,20,26]. The Campylobater-positive rate of broilers turn to increase at ages of 3 to 5 weeks [2].…”
mentioning
confidence: 99%